Simulation-based inference of cell migration dynamics in complex spatial environments - Arruda, Jonas; Alamoudi, Emad; Mueller, Robert; Vaisband, Marc; Molkenbur, Ronja; Merrin, Jack; Kiermaier, Eva; Hasenauer, Jan (npj Systems Biology and Applications)
To assess cell migration in complex spatial environments, microfabricated chips, such as mazes and pillar forests, are routinely used to impose spatial and mechanical constraints, and cell trajectories are followed within these structures by advanced imaging techniques. In systems mechanobiology, computational models serve as essential tools to uncover how physical geometry influences intracellular dynamics; however, decoding such complex behaviors requires advanced inference techniques. Here, we integrated experimental observations of dendritic cell migration in a geometrically constrained microenvironment into a Cellular Potts model. We demonstrated that these spatial constraints modulate the motility dynamics, including speed and directional changes. We show that classical summary statistics, such as mean squared displacement and turning angle distributions, can resolve key mechanistic features but fail to extract richer spatiotemporal patterns, limiting accurate parameter inference. To solve this, we applied neural posterior estimation with in-the-loop learning of summary features. This learned summary representation of the data enables robust and flexible parameter inference, providing a data-driven framework for model calibration and advancing quantitative analysis of cell migration in structured microenvironments.

Marr's three levels for embryonic development: Information, dynamical systems, gene networks - Brückner, David; Tkačik, Gašper (PRX Life)
Developmental patterning comprises processes that range from purely instructed, where external signals specify cell fates, to fully self-organized, where spatial patterns emerge autonomously through cellular interactions. We propose that both extremes—as well as the continuum of intermediate cases—can be conceptualized as information-processing systems, whose operation can be described using “Marr's three levels of analysis”: the computational problem being solved, the algorithms employed, and their molecular implementation. At the first level, we argue that normative theories, such as information-theoretic optimization principles, provide a formalization of the computational problem. At the second level, we show how simplified information-processing architectures provide a framework for developmental algorithms, which are formalized mathematically using dynamical systems theory. At the third level, the implementation of developmental algorithms is described by mechanistic biophysical and gene regulatory network models.

The splicing paralogues SNRPB and SNRPN control differential metabolic states. - Polat Haas, Feyza; Villalba Requena, Ana; Rusina, Polina; Gopalan, Anusha; Fritz, Hector; Akhmetkaliyev, Azamat; Ruehle, Frank; Einsiedel, Anna; Szczepinska, Anna; Kielisch, Fridolin; Chen, Jia-Xuan; Nguyen, Susanne; et al. (bioRxiv)
Gene duplication underlies evolutionary innovation, yet many paralogues remain highly similar, raising questions about their functional divergence and physiological relevance. The spliceosomal Sm core protein SNRPB and its mammalian-specific paralogue SNRPN share over 90% sequence identity, but their distinct expression patterns - SNRPB being ubiquitous and SNRPN confined to the brain - suggest specialized functions. Why mammals have two different spliceosomes has remained obscure. Here, we generated isogenic human cell lines expressing ectopically either SNRPB or SNRPN exclusively and found that SNRPN stabilizes transcripts involved in energy metabolism and mitochondrial function, leading to increased mitochondrial abundance and oxygen consumption. Despite similar spliceosomal interactomes, SNRPN more strongly associates with the PRMT5 methylosome complex and exhibits dynamic arginine methylation in its C-terminal region that is sensitive to translation inhibition and amino acid availability. The SNRPN-dependent transcriptome responds to translation inhibition by stabilizing long, intron-rich genes involved in amino acid and energy metabolism. Our findings reveal a nutrient-sensitive, methylation-dependent mechanism that differentiates the two paralogues. This suggests that SNRPN functions as a metabolic-specialized spliceosomal subunit thereby providing tissue-specific adaptation of RNA processing in mammals.

Lineage origin of spinal cord cell type diversity - Gobeil, Sophie A; Da Silveira Neto, Francisco; Silvestrelli, Giulia; Smits, Matthijs Geert; Streicher, Carmen; Cheung, Giselle T; Hippenmeyer, Simon; Sweeney, Lora Beatrice Jaeger (bioRxiv)
The complexity and specificity of movement in vertebrates is driven by a rich diversity of spinal motor and interneuron cell types. During development, eleven spinal cord progenitor domains generate an equivalent number of cardinal neuron types. How progenitor domains, individual progenitors, and post-mitotic diversity relate is still unknown. We performed high-resolution, single-progenitor cell lineage tracing in the embryonic mouse spinal cord using mosaic analysis with double markers (MADM). Our quantitative study of lineage progression revealed that spinal cord progenitors undergo highly variable numbers of proliferative, neurogenic, and gliogenic cell divisions. The nascent clonally-related neurons migrate radially over large distances, span the dorsoventral axis, and even cross the midline, demonstrating striking bilaterality. Molecular and morphometric analysis indicate high levels of progenitor multipotency, with an individual progenitor capable of producing several molecularly and morphologically distinct neuron types, as well as astrocytes. These findings redefine spinal cord development as a process in which lineage variability — rather than rigid progenitor identity — drives the generation of cellular diversity.

Discontinuous transition to shear flow turbulence - Yang, Bowen; Zhuang, Yi; Yalniz, Gökhan; Vasudevan, Mukund; Marensi, Elena; Hof, Björn (Nature Physics)
Depending on the type of flow, the transition to turbulence can take one of two forms: either turbulence arises from a sequence of instabilities or from the spatial proliferation of transiently chaotic domains, a process analogous to directed percolation. The former scenario is commonly referred to as a supercritical transition and frequently encountered in flows destabilized by body forces, whereas the latter subcritical transition is common in shear flows. Both cases are inherently continuous in a sense that the transformation from ordered laminar to fully turbulent fluid motion is only accomplished gradually with flow speed. Here we show that these established transition types do not account for the more general setting of shear flows subject to body forces. The combination of the two continuous scenarios leads to the attenuation of spatial coupling; with increasing forcing amplitude, the transition becomes increasingly sharp and eventually discontinuous. We argue that the suppression of laminar–turbulent coexistence and the approach towards a discontinuous phase transition potentially apply to a broad range of situations including flows subject to, for example, buoyancy, centrifugal or electromagnetic forces.

Non-equilibrium plasmon liquid in a Josephson junction chain - Bubis, Anton; Vigliotti, Lucia; Serbyn, Maksym; Higginbotham, Andrew P (Science Advances)
Equilibrium quantum systems are often described by a gas of weakly interacting normal modes. Bringing such systems far from equilibrium, however, can drastically enhance mode-to-mode interactions. Understanding the resulting liquid is a fundamental question for quantum statistical mechanics and a practical question for engineering driven quantum devices. To tackle this question, we probe the non-equilibrium kinetics of one-dimensional plasmons in a long chain of Josephson junctions. We introduce multimode spectroscopy to controllably study the departure from equilibrium, witnessing the evolution from pairwise coupling between plasma modes at weak driving to dramatic, high-order, cascaded couplings at strong driving. Scaling to many-mode drives, we stimulate interactions between hundreds of modes, resulting in near-continuum internal dynamics. Imaging the resulting non-equilibrium plasmon populations, we then resolve the nonlocal redistribution of energy in the response to a weak perturbation—an explicit verification of the emergence of a strongly interacting, non-equilibrium liquid of plasmons.

Root system plasticity under nutrient limitation : Investigating hormonal and molecular drivers in Arabidopsis thaliana and Coffea species - Riegler, Stefan

Thesis Data for Root System Plasticity under Nutrient Limitation: Investigating Hormonal and Molecular Drivers in Arabidopsis thaliana and Coffea species - Riegler, Stefan
The data contains information on coffee differential gene expression as well as co-expression and trait correlations in two separate experiments. First, contrasting nitrogen supply, second, intra- and interspecific grafting.

Phenomenological model of decaying Bose polarons - Al Hyder, Ragheed; Bruun, G. M.; Pohl, T.; Lemeshko, Mikhail; Volosniev, Artem (Physical Review Research)
Cold atom experiments show that a mobile impurity particle immersed in a weakly interacting Bose-Einstein condensate forms a well-defined quasiparticle (Bose polaron) for weak to moderate impurity-boson interaction strengths, whereas a significant line broadening is consistently observed for strong interactions. Motivated by this, we introduce a phenomenological theory based on the assumption that the most relevant states are characterized by the impurity correlated with at most one boson, since they have the largest overlap with the uncorrelated states to which the most common experimental probes couple. These experimentally relevant states can, however, decay to lower energy states characterized by correlations involving multiple bosons, and we model this using a minimal variational wave function combined with a complex impurity-boson interaction strength. We first motivate this approach by comparing to a more elaborate theory that includes correlations with up to two bosons. Our phenomenological model is shown to recover the main results of two recent experiments probing both the spectral and the nonequilibrium properties of the Bose polaron. Our work offers an intuitive framework for analyzing experimental data and highlights the importance of understanding the complicated problem of the Bose polaron decay in a many-body setting.

Flexoelectric domain walls enable charge separation and transport in cubic perovskites - Rak, Dmytro; Lorenc, Dusan; Balazs, Daniel; Zhumekenov, Ayan A.; Bakr, Osman M.; Alpichshev, Zhanybek (Nature Communications)
The exceptional energy-harvesting efficiency of lead-halide perovskites arises from unusually long photocarrier diffusion lengths and recombination lifetimes that persist even in defect-rich, solution-grown samples. Paradoxically, perovskites are also known for having very short exciton decay times. Here, we resolve this apparent contradiction by showing that key optoelectronic properties of perovskites can be explained by localized flexoelectric polarization confined to interfaces between domains of spontaneous strain. Using birefringence imaging, electrochemical staining, and zero-bias photocurrent measurements, we visualize the domain structure and directly probe the associated internal fields in nominally cubic single crystals of methylammonium lead bromide. We demonstrate that localized flexoelectric fields spatially separate electrons and holes to opposite sides of domain walls, exponentially suppressing recombination. Domain walls thus act as efficient mesoscopic transport channels for long-lived photocarriers, microscopically linking structural heterogeneity to charge transport and offering mechanistically informed design principles for perovskite solar-energy technologies.

Modelling chemotaxis of branched cells in complex environments provides insights into immune cell navigation - Liu, Jiayi; Ron, Jonathan E.; Rinaldi, Giulia; Williantarra, Ivanna; Georgantzoglou, Antonios; de Vries, Ingrid; Sixt, Michael K; Sarris, Milka; Gov, Nir S. (PLOS Computational Biology)
Cell migration in vivo is often guided by chemical signaling, i.e., chemotaxis. For immune cells performing chemotaxis in the organism, this process is influenced by the complex geometry of the tissue environment. In this study, we use a theoretical model of branched cell migration on a network to explore the cellular response to chemical gradients. The model predicts the response of a branched cell to a chemical gradient: how the cell reorients its internal polarity and how it navigates through a complex environment up a chemical gradient. We then compare the model’s predictions with experimental observations of neutrophils migrating to the site of a laser-inflicted wound in a zebrafish larva fin, and neutrophils migrating in vitro inside a regular lattice of pillars. We find that the model captures the details of the subcellular response to the chemokine gradient, as well as qualitative characteristics of the large-scale migration, suggesting that the neutrophils behave as fast cells, which explains the functionality of these immune cells.

Maximum persistent Betti numbers of Čech complexes - Edelsbrunner, Herbert; Kahle, Matthew; Kanazawa, Shu (Journal of Applied and Computational Topology)
This note proves that only a linear number of holes in a Cech complex of n points in R^d can persist over an interval of constant length. Specifically, for any fixed dimension p < d and fixed ε > 0, the number of p-dimensional holes in the ˇ Cech complex at radius 1 that persist to radius 1+ε is bounded above by a constant times n,where n is the number of points. The proof uses a packing argument supported by relating theCˇ ech complexes with corresponding snap complexes over the cells in a partition of space. The argument is self-contained and elementary, relying on geometric and combinatorial constructions rather than on the existing theory of sparse approximations or interleavings. The bound also applies to Alpha complexes and Vietoris–Rips complexes. While our result can be inferred from prior work on sparse filtrations, to our knowledge, no explicit statement or direct proof of this bound appears in the literature.

The evolutionary genomics of meiotic drive - Presgraves, Daven C.; Dawe, R. Kelly; Dyer, Kelly A.; Fishman, Lila; Bhide, Soumitra A.; Bradshaw, Sasha L.; Brady, Meghan J.; Burga, Alejandro; Courret, Cécile; Fagen, Brandon L.; Machado Ferretti, Ana Beatriz Stein; Kelemen, Réka K; et al. (Molecular Biology and Evolution)
Meiotic drivers are selfish genetic elements that gain transmission advantages by distorting equal, Mendelian segregation. For decades, biologists have considered meiotic drivers as interesting, albeit esoteric, case studies. It is now clear, however, that meiotic drive is more common and phylogenetically widespread than previously supposed. Indeed, intensive study of a few well-known cases has begun to reveal the evolutionary genomic consequences of meiotic drive. We argue here that many features of genome evolution, content, and organization that are seemingly inexplicable by organismal adaptation or nearly neutral processes are instead best accounted for by recurrent histories of meiotic drive. We review how meiotic drive can affect the evolution of sequences, gene copy numbers, genes with functions in meiosis and gametogenesis, signatures of “selection,” chromosome rearrangements, and karyotype evolution. We also explore the interactions of meiotic drive elements with other classes of selfish genetic elements, including satellite DNAs, transposable elements, and with the endogenous host genes involved in drive suppression. Finally, we argue that some aspects of drive-mediated genome evolution are now sufficiently well established that we might reverse the direction of discovery—rather than ask how drive affects genome evolution, we can use genome data to discover new putative drive elements.

CA3Simu v1.06 (vargas2026v1) - Schlögl, Alois
Keywords: hypocampus; ca3 simulations; modelling

Privacy-preserving runtime verification - Karimi, Mahyar
Runtime verification offers scalable solutions to improve the safety and reliability of systems. However, systems that require verification or monitoring by a third party to ensure compliance with a specification might contain sensitive information, causing privacy concerns when usual runtime verification approaches are used. Privacy is compromised if protected information about the system, or sensitive data that is processed by the system, is revealed. In addition, revealing the specification being monitored may undermine the essence of third-party verification. In this thesis, we propose a protocol for privacy-preserving runtime verification of systems against formal sequential specifications. We develop the protocol in two steps. In the first step, the monitor verifies whether the system satisfies the specification without learning anything else, though both parties are aware of the specification. In the second step, we extend the protocol to ensure that the system remains oblivious to the monitored specification, while the monitor learns only whether the system satisfies the specification and nothing more. Our protocol adapts and improves existing techniques used in cryptography, and more specifically, multi-party computation. The sequential specification defines the observation step of the monitor, whose granularity depends on the situation (e.g., banks may be monitored on a daily basis). Our protocol exchanges a single message per observation step, after an initialization phase. This design minimizes communication overhead, enabling relatively lightweight privacy-preserving monitoring. We implement our approach for monitoring specifications described by register automata and evaluate it experimentally.
Keywords: Privacy-preserving verification; Runtime verification; Monitoring; Reactive functionalities; Cryptographic protocols

One-milligram torsional pendulum toward experiments at the quantum-gravity interface - Agafonova, Sofya; Rosello, Pere; Mekonnen, Manuel; Hosten, Onur (Communications Physics)
Probing the possibility of entanglement generation through gravity offers a path to tackle the question of whether gravitational fields possess a quantum mechanical nature. A potential realization necessitates systems with low-frequency dynamics at an optimal mass scale, for which the microgram-to-milligram range is a strong contender. Here, after refining a figure-of-merit for the problem, we present a 1-milligram torsional pendulum operating at 18 Hz. We demonstrate laser cooling its motion from room temperature to 240 microkelvins, surpassing by over 20-fold the coldest motions attained for oscillators ranging from micrograms to kilograms. We quantify and contrast the utility of the current approach with other platforms. The achieved performance and large improvement potential highlight milligram-scale torsional pendulums as a powerful platform for precision measurements relevant to future studies at the quantum-gravity interface.

ALTAA: Analysis of long-term activity patterns in ant colonies - Oh, Jinook; Cremer, Sylvia (Methods in Ecology and Evolution)
1. Collective behaviours are a fascinating study area due to the emergent properties that can only arise in groups of interacting individuals. However, their quantitative study is often impaired by technical difficulties, creating either low-quality and sparse data or impractical data amounts, particularly when capturing large groups over long periods of time. Common challenges arise from recording group members with as little obscuring of each other as possible, as well as in generating manageable data amounts with as high as possible information content. 2. We here provide a multicomponent system that allows to record, analyse and simulate the long-term spatiotemporal activity patterns of insect collectives, especially ant colonies. Our Ant Observing System, ALTAA, comprises a flat-nest design to prevent occlusion of individuals, a recording system running on a low-power single-board-computer, and a set of computer programmes performing quantitative analyses to guide the formation and validation of rules underlying the observed collective patterns. Our system is scalable in that it allows parallel, continuous observation of a high number of colonies using low memory space, with colony maintenance requirements (e.g. feeding, nest humidity) being achieved at lowest possible disturbance by the experimenter. 3. We showcase the potential of the system in a study using the black garden ant, Lasius niger, where we analyse the spatiotemporal effects of different group sizes (1, 6, 10 ants), brood (larvae) presence or absence, as well as of different nest geometries, over a period of 1 week. We show that the ants' motion activity has a weak periodicity in the range of 20 to 120 min promoted by larval presence, and that ants are spatially attracted to their larvae, the water source and the walls. We also find that the presence of nestmates lowers an individual ant's motion activity. Observed data are compared to simulations of the temporal activity of the ants. 4. ALTAA provides a powerful toolkit to quantify and interpret spatial and temporal collective activity patterns in (social) insects over extended periods.

Geometry-driven asymmetric cell divisions pattern cell cycles and zygotic genome activation in the zebrafish embryo - Mishra, Nikhil; Li, Yuting I; Hannezo, Edouard B; Heisenberg, Carl-Philipp J (Nature Physics)
Early embryo geometry is one of the most invariant species-specific traits, yet its role in ensuring developmental reproducibility and robustness remains underexplored. Here we show that in zebrafish, the geometry of the fertilized egg—specifically its curvature and volume—serves as a critical initial condition triggering a cascade of events that influence development. The embryo geometry guides patterned asymmetric cell divisions in the blastoderm, generating radial gradients of cell volume and nucleocytoplasmic ratio. These gradients generate mitotic phase waves, with the nucleocytoplasmic ratio determining individual cell cycle periods independently of other cells. We demonstrate that reducing cell autonomy reshapes these waves, emphasizing the instructive role of geometry-derived volume patterns in setting the intrinsic period of the cell cycle oscillator. In addition to organizing cell cycles, early embryo geometry spatially patterns zygotic genome activation at the midblastula transition, a key step in establishing embryonic autonomy. Disrupting the embryo shape alters the zygotic genome activation pattern and causes ectopic germ layer specification, underscoring the developmental significance of geometry. Together, our findings reveal a symmetry-breaking function of early embryo geometry in coordinating cell cycle and transcriptional patterning.

Anomalous multigap topological phases in periodically driven quantum rotors - Karle, Volker; Lemeshko, Mikhail; Bouhon, Adrien; Slager, Robert-Jan; Ünal, F. Nur (Physical Review A)
We demonstrate that periodically driven quantum rotors provide a promising and broadly applicable platform to implement multigap topological phases, where groups of bands can acquire topological invariants due to non-Abelian braiding of band degeneracies. By adiabatically varying the periodic kicks to the rotor we find nodal-line braiding, which causes sign flips of topological charges of band nodes and can prevent them from annihilating, indicated by nonzero values of the patch Euler class. In particular, we report on the emergence of an anomalous Dirac string phase arising in the strongly driven regime, a truly out-of-equilibrium phase of the quantum rotor. This phase emanates from braiding processes involving all (quasienergy) gaps and manifests itself with edge states at zero angular momentum. Our results reveal direct applications in state-of-the-art experiments of quantum rotors, such as linear molecules driven by periodic far-off-resonant laser pulses or artificial quantum rotors in optical lattices, whose extensive versatility offers precise modification and observation of novel non-Abelian topological properties.

Geometry-driven self-organization of migrating cells and chiral filaments - Dunajova, Zuzana